INTEGRATION OF NATIVE GENETIC RESOURCES IN BRAZILIAN AGROFORESTRY SYSTEMS - Stipp Paterniani, Maria Lidia [UNESP]; Pardini, Andrea; Pratesi, Valentina; Kellimore, L. R. (Nova Science Publishers, Inc, 2009)
Genetic resources can be considered the most important component of agroforestry systems, in fact the success of these systems depends largely on appropriate combination of genetic components (plant and animal species) and their adaptation to environmental parameters (rainfall, temperature, light, soil). Agroforestry systems share biological diversity and dynamical structure. Genetic diversity in natural or agricultural systems, favours continuous adaptation of plants to environmental changes, as well as adaptation of ecotypes to specific conditions and selection of highly productive cultivars. This paper introduces examples of utilization of Brazilian genetic resources in agroforestry systems of three large Brazilian biomes: Amazonia, Cerrado and Caatinga. Amazonia biome represents an area of about 60% of the national territory. It comprises the richest tropical biodiversity in the world. In this region, slash-and-burn native vegetation is a common practice to establish agriculture and livestock farming. Agroforestry systems are good alternatives to this system, since they are able to provide higher yields to farmers and, at the same time, can conserve the integrity of the forest vegetation better than specialized farming systems. Cerrado biome, the second largest area, covers 25% of the national territory. This biome represents the largest and richest savannahs area in the world. Currently, this region is important for production of cereals, meat and milk. The association of forest plantations with crops and pastures has increased the productivity of the land and substantially reduced soil erosion and other negative effects of environmental exploitation. Caatinga biome is an exclusively Brazilian biome, rich of endemic vegetation and covering 11% of the country. Rich diversity of small trees, shrubs, grasses, legumes, succulents including many Cactaceae species are found. But the ecosystem is highly fragile and factors such as low soil fertility and limited water availability make high yields not possible. In this context, agroforestry would be particularly appropriated to improve soil quality and promote a sustainable food production, particularly useful to smallholders that live in this semiarid region. The advantages and constrains of agroforestry systems establishment in each of these three biomes are introduced, and the importance of genetic resources in implementing complex systems will be discussed, including suggestions to increase food production and to improve quality of life in sustainable ways.